“Oxford housewife” or the only british woman to have ever won the Nobel Prize in science? – Dorothy Hodgkin - V. M. Danilova; S. G. Torkhova; S. V. Komisarenko (The Ukrainian Biochemical Journal, 2024)
Dorothy Crowfoot Hodgkin, a British chemist and Nobel Prize winner, who extended the method of X-ray crystallography to determine the structure of biomolecules that furthered the development of structural biology. In 1964, she was awarded the Nobel Prize in Chemistry “for the determinations by X-ray techniques of the structures of important biochemical substances”, particularly vitamin B12 and antibiotic penicillin. Five years after winning the Nobel Prize, Dorothy Hodgkin also established the structure of insulin. Although The Daily Mail headlined her as an “Oxford housewife”, Dorothy Hodgkin overcame gender inequality to become the third woman in history to win the Nobel Prize in Chemistry and remains the only British woman researcher to be awarded the most prestigious prize in the sciences.